On the Deconstructive Logic of Populism - Gandesha, Samir (Scenari, 2021)
This article examines Ernesto Laclau’s deconstructive account of populism. Such an account is premised on the notion that politics entails the institution of the “social”. In other words, politics stabilizes in a provisional and temporary way, the inherently heterogenous, infinitely deferring and differing logic of the social space. The article argues that Laclau over-emphasizes such heterogeneity and this becomes particularly evident when we consider the momentous challenges faced by populist parties in power such as that of Syriza in its confrontation with the Troika in the aftermath of the 2015 Referendum.